2018
DOI: 10.4103/jpbs.jpbs_215_17
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotic effect of red cabbage (Brassica oleracea) on pentobarbital-induced sleep in mice

Abstract: Objective:The present study was performed to investigate the effect of hydroalcoholic extract of red cabbage and its fractions on sleeping behavior in mice.Materials and Methods:The extract and its fractions were injected to mice and sleep duration as well as sleep latency were recorded. Furthermore, toxicity of the extract was determined both in vivo and in vitro.Results:The extract increased sleep duration at doses of 50–200mg/kg (P < 0.001). This observed hypnotic effect was comparable to that of diazepam (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Other studies found that different polyphenols modulated sleep via GABA receptors. Polyphenols such as phlorotannins [203,204] and triphlorethol A (seaweed polyphenols) [216], red cabbage extracts [217], and kiwifruit extracts [206] decreased SOL and increased sleep duration via GABA receptors in mice. Other polyphenols such as bioflavonoids extracts from Rhus parviflora referred as Tintidikah, a medicinal plant used in south Asia, were the most potent components in decreasing SOL and increasing sleep duration via GABA receptors [205].…”
Section: Mechanisms For the Relationship Between Sleep And Fruit Amentioning
confidence: 99%
“…Other studies found that different polyphenols modulated sleep via GABA receptors. Polyphenols such as phlorotannins [203,204] and triphlorethol A (seaweed polyphenols) [216], red cabbage extracts [217], and kiwifruit extracts [206] decreased SOL and increased sleep duration via GABA receptors in mice. Other polyphenols such as bioflavonoids extracts from Rhus parviflora referred as Tintidikah, a medicinal plant used in south Asia, were the most potent components in decreasing SOL and increasing sleep duration via GABA receptors [205].…”
Section: Mechanisms For the Relationship Between Sleep And Fruit Amentioning
confidence: 99%